Speakers for the Dead: Star Trek, The Holocaust, and the Representation of Atrocity. - Kapell, Matthew (Extrapolation (Kent State University Press))
Examines the thematic content of the science fiction television program `Star Trek: Deep Space Nine.' Representation of death and atrocity in the TV program; Allusions drawn from the period of World War Two; Evocation of the Jewish culture to the characters of the Bajorans; Comparison between the Bajoran Holocaust and the Jewish Holocaust.